IMPROVING PHYSICAL EDUCATION AND MASS SPORTS EVENTS AMONG STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes modern approaches to organizing physical education classes and mass sports events in higher education institutions. The study focuses on promoting a healthy lifestyle among students, increasing their physical activity, and developing sports culture from both scientific-theoretical and methodological perspectives. The research proposes methods for effectively organizing physical education classes, conducting mass sports events using innovative approaches, and integrating digital technologies into sports activities. The results indicate that systematically organized sports events significantly enhance students' physical fitness, health, and social activity.